Influence of an Offshore Mussel Aquaculture Site on the Distribution of Epibenthic Macrofauna in Îles de la Madeleine, Eastern Canada - Sean, Anne-Sara; Drouin, Annick; Archambault, Philippe; McKindsey, Christopher W. (Frontiers in Marine Science, 2022)
Mussel farming influences benthic environments by organic loading and the addition of physical structure within aquaculture leases. This study evaluated near-field (distance to mussel aquaculture structures, line-scale) and bay-scale (inside vs. outside a blue mussel, Mytilius edulis, farm) effects of an offshore mussel farm in Îles de la Madeleine (Canada) on epibenthic macrofaunal communities. Benthic communities were evaluated by underwater visual counts using SCUBA in June and July 2014. The mussel farm influenced benthic communities at line- and bay-scales. Overall, crabs (Cancer irroratus, Pagarus pubecsens, Pagarus acadianus), sea stars (Asterias rubens), Northern moon snails (Polinices heros), and American lobsters (Homarus americanus) were more abundant in farm sites than outside of farm sites and ocean quahogs (Arctica islandica) were more abundant outside. No clear spatial trend was observed for winter flounder (Pseudopleuronectes americanus) and the sand dollar (Echinarachnius parma) but both species differed (flounder) or showed a trend to differ (sand dollar) between sampling dates. Spatial structure in the distribution of macrofauna was evident within the aquaculture lease as most species were more abundant directly below and close to mussel lines and anchor blocks. There was no spatial structure in non-farm sites. Further investigation is needed to evaluate if mussel farms serve as ecological traps for the species that congregate within them. The long-term effects of the observed spatial effects of offshore mussel culture on macrofauna fitness remains unknown.